Pelatihan Penerapan Instrumen HAM Internasional: Konvensi Hak Anak bagi Pemerintah Daerah dan Lembaga Pemerhati Anak di Sumatera Utara - Zuliah, Azmiati (Civiliza Publishing, 2025)
Training on the implementation of international Human Rights (HR) instruments, particularly the Convention on the Rights of the Child (CRC), is essential for local governments and child-focused institutions in strengthening child protection systems. This community service program aimed to enhance the capacity and understanding of local government officials and relevant institutions in integrating CRC principles into policy formulation and the provision of child protection services in North Sumatra. The activities were carried out through lectures, group discussions, case-based analyses, and policy simulation exercises. Evaluation results indicate a significant improvement in participants’ knowledge, their comprehension of CRC principles, and their ability to identify child rights violations and develop appropriate policy responses. Overall, this program directly contributes to reinforcing child protection mechanisms at the local level in accordance with international human rights standards